2019
DOI: 10.24059/olj.v23i4.1613
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Instructional Approaches in Online Technical Education in Community Colleges

Abstract: Technical education programs in community colleges prepare students for many science and engineering-based jobs in the United States. An increasing number of technical education programs in community colleges are using online learning tools to teach courses. However, little is currently known about the ways these programs are integrating online learning in their coursework. This study examined fifteen National Science Foundation funded technical education programs that use online learning to partially or entir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In post-secondary education, there is a variety of instructional approaches adopted. Horvitz et al, (2019) identified four categories of instructional approaches in community colleges in the United States, these included: (a) a hybrid or blended course with asynchronous online lecturers; (b) a hybrid or blended course with synchronous lectures; (c) a hybrid or blended course with a combination of asynchronous and synchronous lectures and discussions; and (d) a course that is fully online (pp. 241-242).…”
Section: Digital Technologies and Instructional Approachesmentioning
confidence: 99%
“…In post-secondary education, there is a variety of instructional approaches adopted. Horvitz et al, (2019) identified four categories of instructional approaches in community colleges in the United States, these included: (a) a hybrid or blended course with asynchronous online lecturers; (b) a hybrid or blended course with synchronous lectures; (c) a hybrid or blended course with a combination of asynchronous and synchronous lectures and discussions; and (d) a course that is fully online (pp. 241-242).…”
Section: Digital Technologies and Instructional Approachesmentioning
confidence: 99%
“…The methodological approach on teaching STEM has recently evolved in education from using traditional media to more advanced technological media [44,45]. Moreover, more and more studies are associated with other teaching methods considered innovative, such as online learning, gamification, learning communities, design-based science education or augmented reality [46][47][48][49][50][51]. This methodology brings to the educational field another active teaching method, which allows to develop the competences of the students towards the society [28].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some universities and instructors have been experimenting with the new modality since shortly before the pandemic. For instance, Horvitz et al (2019, p. 237) identify “a hybrid or blended course with a combination of asynchronous and synchronous lectures and discussions” as one of the four instructional approaches adopted in U.S. community colleges. On the website of Kansas State University (n.d.), simple strategies for synchronous and asynchronous online teaching are highlighted.…”
Section: Literature Reviewmentioning
confidence: 99%